IRCAD recommendation on safe laparoscopic cholecystectomy. (27th October 2017) - Conrad, Claudius; Wakabayashi, Go; Asbun, Horacio J.; Dallemagne, Bernard; Demartines, Nicolas; Diana, Michele; Fuks, David; Giménez, Mariano Eduardo; Goumard, Claire; Kaneko, Hironori; Memeo, Riccardo; Resende, Alexandre; et al.
Abstract: An expert recommendation conference was conducted to identify factors associated with adverse events during laparoscopic cholecystectomy (LC) with the goal of deriving expert recommendations for the reduction of biliary and vascular injury. Nineteen hepato‐pancreato‐biliary (HPB) surgeons from high‐volume surgery centers in six countries comprised the Research Institute Against Cancer of the Digestive System (IRCAD) Recommendations Group. Systematic search of PubMed, Cochrane, and Embase was conducted. Using nominal group technique, structured group meetings were held to identify key items for safer LC. Consensus was achieved when 80% of respondents ranked an item as 1 or 2 (Likert scale 1–4). Seventy‐one IRCAD HPB course participants assessed the expert recommendations which were compared to responses of 37 general surgery course participants. The IRCAD recommendations were structured in seven statements. The key topics included exposure of the operative field, appropriate use of energy device and establishment of the critical view of safety (CVS), systematic preoperative imaging, cholangiogram and alternative techniques, role of partial and dome‐down (fundus‐first) cholecystectomy. Highest consensus was achieved on the importance of the CVS as well as dome‐down technique and partial cholecystectomy as alternative techniques. The put forward IRCAD recommendations may help to promote safe surgical practice of LC and initiate specific training to avoid adverse events. Abstract : Highlight An international structured expert recommendation conference for safe laparoscopic cholecystectomy was conducted. Critical recommendations were divided into 7 statements. The highest consensus was achieved on the importance of the critical view of safety and alternative surgical techniques (dome‐down technique, and partial cholecystectomy).